Education of national minorities in primary schools in the Republic of Serbia - Jovanović, Marko; Joković, Milica (Sociološki pregled, 2023)
The position taken in this paper is that the development of a society depends on the status, role and importance of the educational system, and that education has a significant impact on personality formation. The aim of this paper is to establish the condition of primary school education for members of national minorities and, based on this, to enable getting a better insight into steps to be taken in order to remove regulatory and practical shortcomings. Three models of primary school education in the languages of national minorities have been analysed: entire education in one of eight languages of national minorities, with Serbian as a non-mother tongue as a compulsory subject; entire education in the Serbian language with an option to take an elective subject/programme with elements of national culture (in the mother tongue); and bilingual education in Serbian and in the language of a national minority. Furthermore, empirical argumentation is presented for the period covering the academic years 2013/14 through to 2020/21. In the conclusion of this paper, it is noted that capacities of the educational system should be strengthened by introducing professional training for teachers of the languages of national minorities, which would ensure the availability of competent teaching staff. Additionally, appropriate curricula, textbooks and other teaching aids required for the learning of minority languages should be improved, in accordance with the latest teaching methods.